Highly efficient soluble expression and purification of recombinant human basic fibroblast growth factor (hbFGF) by fusion with a new collagen-like protein (Scl2) in Escherichia coli - Rahman, Inamur; Fang, Lina; Wei, Zhang; Zheng, Xiaodong; Jiazhang, Lian; Huang, Lei; Xu, Zhinan (Preparative biochemistry & biotechnology, 2020)
Human basic fibroblast growth factor (hbFGF) is involved in a wide range of biological activities that affect the growth, differentiation, and migration. Due to its wound healing effects and therapy, hbFGF has the potential as therapeutic agent. Therefore, large-scale production of biologically active recombinant hbFGF with low cost is highly desirable. However, the complex structure of hbFGF hinders its high-level expression as the soluble and functional form. In the present study, an efficient, cost-effective, and scalable method for producing recombinant hbFGF was developed. The modified collagen-like protein (Scl2-M) from Streptococcus pyogenes was used as the fusion tag for producing recombinant hbFGF for the first time. After optimization, the expression level of Scl2-M-hbFGF reached approximately 0.85 g/L in the shake flask and 7.7 g/L in a high cell-density fermenter using glycerol as a carbon source. Then, the recombinant Scl2-M-hbFGF was readily purified using one-step acid precipitation and the purified Scl2-M-hbFGF was digested with enterokinase. The digested mixture was further subject to ion-exchange chromatography, and the final high-purity (96%) hbFGF product was prepared by freeze-drying. The recovery rate of the whole purification process attained 55.0%. In addition, the biological activity of recombinant hbFGF was confirmed by using L929 and BALB/c3T3 fibroblasts. Overall, this method has the potential for large scale production of recombinant hbFGF.